My own patient experience: Learning to walk again like a baby - Ozcirpici, Birgul (Archives of Community Medicine and Public Health, 2018)
I had a left monoparalysis during a holiday abroad in July 2005. This narrative shares my experience of getting ill in a foreign country, how it is difficult to describe your troubles and, how little is known about the long recovery period of paralysis by physicans. My experience showed me that being a patient was so far from being a doctor. Social support is very important during recovery from paralysis, because you can not do anything by yourself and you are very desperate. You feel the muscles that have not gained tonus yet, like a belt and strap. Only the physiotherapist, warned me about the long recovery progress. I did not realizse how high the sidewalks are. A 1 cm height feels like a mountain to climb, and a 1 kg weight like a truck to carry. From this experince, I offer two main suggestions including 1) Language is very important for foreign patients for communication at hospitals. An online translation center for hospitals, that translators of each language work, may be benefical when it is needed at any country. 2) Be clear in communicating with patients about their diagnosis, in this case telling the patient having paralysis how long the recovery period will be in detail.